Climate change impacts and adaptation strategies: A case study in Northern Vietnam - Khuat Huyen; Ha Tuan (BIO Web of Conferences)
Climate change and its impacts have become increasingly evident in the disaster-prone country like Vietnam. This study was conducted in a mountainous province in the northern part of the country to understand impacts of climate change on the livelihoods of smallholder farmers and identify key strategies toward climate resilience. Through stakeholder surveys and interactive processes among local farmers and relevant stakeholders, a number of locally appropriate climate-resilient models and practices have been identified. In addition, an overall strategy with identified systemic interventions, through the support of a decision supporting tool, have been formulated in addressing the climate induced risks. This study provided strong rationale for policy recommendations and future research on multiple benefits of the identified climate-resilient models and practices.